Ottoman Rule in Damascus, 1708-1758 - Barbir, Karl K., 1948- (Book collections on Project MUSE., 1980)
On the basis of new evidence from the Ottoman archives in Istanbul, Karl Barbir challenges the current interpretation of Ottoman rule in Damascus during the eighteenth century. He argues that the prevailing themes of decline and stagnation--usually applied to the entire century--in fact apply only to the latter half of the century. This discovery, he contends, affords a more balanced and realistic view of the Near East's Ottoman past than previous studies have suggested. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.